EFEKTIVITAS PEMBELAJARAN BERBASIS STEAM DALAM PEMBUATAN TERARIUM MINI SEDERHANA TERHADAP PEMAHAMAN KETERAMPILAN PROSES SAINS DALAM MATERI EKOSISTEM PADA SISWA KELAS III SD NEGERI 112 PEKANBARU - Rahma, Ade; Nafisha; Elsa Oktavia , Resti; Hermita, Neni; Gusmida Syahrun Barokah , Rifqa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effectiveness of STEAM-based (Science, Technology, Engineering, Art, and Mathematics) learning through a mini terrarium project in improving elementary students' science skills. The research employed a quantitative approach with a quasi-experimental design (one-group pretest-posttest) involving 17 third-grade students at SD Negeri 112 Pekanbaru. The instruments used included learning outcome tests (pretest and posttest) and STEAM skills observation sheets. Data were analyzed using descriptive statistics, N-Gain test, and paired sample t-test. The results showed an increase in the average student score from 56 to 70, with an N-Gain value of 0.29 categorized as low but approaching moderate. Qualitatively, students demonstrated improvements in observation, classification, collaboration, and communication skills. Project-based learning through mini terrarium creation proved effective in helping students understand ecosystem concepts concretely and increasing learning engagement. Therefore, the STEAM approach has strong potential as an innovative learning strategy to enhance elementary students’ science process skills.